2020
DOI: 10.7150/thno.46467
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan-functionalized Selenium Nanoparticles target Tumor Cell Mitochondria via TLR4/TRAF3/MFN1 pathway

Abstract: Rationale: Malignant ascites caused by cancer cells results in poor prognosis and short average survival time. No effective treatment is currently available for malignant ascites. In this study, the effects of lentinan (LNT)-functionalized selenium nanoparticles (Selene) on malignant ascites were evaluated. Furthermore, the mechanism of Selene targeting mitochondria of tumor cells were also investigated. Methods: Selene were synthesized and characterized by TEM, AFM and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…To study the selective toxicity of different isoform-selective HDACIs on ascites cells, the class I selective HDACI MS275, the class II selective HDACI MC1568 and the broad-spectrum HDACI SAHA were chosen to test the cytotoxicity to ascites cells. Because primary peritoneal carcinoma is rare [ 20 , 21 ] and malignant ascites are mainly originated from different metastatic peritoneal carcinoma, here we chose 3 different ascites cell. S180, H22 and EAC are murine sarcoma cancer cell, murine hepatocarcinoma cell, and murine mammary adenocarcinoma cell respectively, and the related ascites model induced by these cells are commonly used [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the selective toxicity of different isoform-selective HDACIs on ascites cells, the class I selective HDACI MS275, the class II selective HDACI MC1568 and the broad-spectrum HDACI SAHA were chosen to test the cytotoxicity to ascites cells. Because primary peritoneal carcinoma is rare [ 20 , 21 ] and malignant ascites are mainly originated from different metastatic peritoneal carcinoma, here we chose 3 different ascites cell. S180, H22 and EAC are murine sarcoma cancer cell, murine hepatocarcinoma cell, and murine mammary adenocarcinoma cell respectively, and the related ascites model induced by these cells are commonly used [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because primary peritoneal carcinoma is rare [ 20 , 21 ] and malignant ascites are mainly originated from different metastatic peritoneal carcinoma, here we chose 3 different ascites cell. S180, H22 and EAC are murine sarcoma cancer cell, murine hepatocarcinoma cell, and murine mammary adenocarcinoma cell respectively, and the related ascites model induced by these cells are commonly used [ 21 , 22 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lentinan‐SeNPs act by enhancing ROS and decreasing the mitochondrial membrane potential, thereby inducing caspase‐3 expression and reduction of ATP levels, while decreasing the expression of several inflammatory cytokines (IL‐1 β , IL‐6, and TNF‐ α ), which led to cell shrinkage and formation of apoptotic bodies. [ 227 ] The anticancer properties of SeNPs stabilized with another fungus polysaccharide, PUP, were also studied. PUP‐SENPs successfully inhibited several cancer cell lines (HT29, HeLa, HepG2, and MDA‐MB‐231) proliferation in a dose‐dependent manner, with no apparent toxicity towards normal cells.…”
Section: Senps For Pharmaceutical Applicationsmentioning
confidence: 99%
“…Liu et al [120] studied the effects of lentinan (LNT)-functionalized selene nanoparticles on malignant ascites. Ovarian malignancy is the most common cause of malignant ascites, which is why OVCAR-3 human ovarian cancer cells were used in this study, along with EAT, a common tumor ascites model [121].…”
Section: Lentinanmentioning
confidence: 99%
“…In contrast to SeNP, which induced pyroptosis because of being taken up by lysosomes, it was shown that Selene was mainly taken up by the mitochondria, thereby inhibiting inflammatory cytokine secretion in ascites. The authors concluded that Selene is effective for treating malignant ascites and may be developed as a clinical drug [120].…”
Section: Lentinanmentioning
confidence: 99%